Evaluasi Peran Panitia Pengawas Pemilu Kecamatan Kutoarjo Kabupaten Purworejo Pada Pemilihan Kepala Daerah Tahun 2024 - Muyasaroh, Kun Maisarotun; Susanti, Martien Herna (Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analytically describe the role of the Election Supervisory Committee (Panwaslu) of Kutoarjo District in overseeing each stage of the 2024 Regional Head Election (Pilkada). The research employs a qualitative approach with a descriptive method, enabling the researcher to explore meanings, experiences, and social dynamics that cannot be measured using quantitative approaches. Primary data were obtained through in-depth interviews with the Chairperson of the Kutoarjo District Panwaslu, supported by direct observation and document studies. The informant was selected using purposive sampling, considering that the Chairperson of Panwaslu has direct knowledge and experience in conducting Pilkada supervision.The results of the study indicate that Panwaslu of Kutoarjo District plays a strategic role in ensuring that each stage of Pilkada is implemented in accordance with democratic principles, justice, and legal regulations. This role is realized through supervision of all stages, including voter data updating, the formation of ad hoc bodies, the campaign period, logistics distribution, as well as voting and vote counting. In addition, Panwaslu carries out preventive functions through socialization, written appeals, surveillance patrols, and cross-sector coordination. In terms of enforcement, Panwaslu responds to every reported violation promptly, transparently, and accountably in accordance with legal procedures. The evaluation of Panwaslu’s role implementation shows that supervision has been carried out optimally despite challenges such as limited supervisory personnel and geographical constraints. This study recommends strengthening human resource capacity, adding supervisory personnel, optimizing information technology, and increasing community participation in election supervision to improve the quality of future Pilkada.